Do strategic alliances in the airline industry create value? - Fernandes, Bernardo Rodrigues de Sousa (2015)
Bernardo Rodrigues de Sousa Fernandes. “Do Strategic Alliances in the Airline Industry Create Value?” This paper investigates airlines’ stock price response to the announcement that an airline is going to join an airline alliance. The paper attempts to evaluate whether or not strategic alliances create value for airline companies. On the three major global airline alliances we were able to observe a positive average cumulative abnormal return from the day of the announcement up to 6 trading days after the announcement. Evidence was found to support that strategic alliances in the airline industry create value for new members. However, for existing alliance members no evidence was found to support that new members entering the alliance create value for existing members.